Pertumbuhan Dan Hasil Tanaman Padi Sawah (Oryza Sativa L.) Pada Duavarietas Dan Jarak Tanam Di Kecamatan Palolo Kabupaten Sigi - Simson Simson; Mahfudz Mahfudz; Sakka Samudin (Mitra Sains, 2019)
The research aims to examine the interaction between varieties and plant spacing of rice and the growth and yield of rice crops with different varieties and different plant spacing. This research arranged in two factors of randomized block design. The first factor was the treatment of two varieties (V) consist of: V1 = Cisantana Varieties,V2 = Ciherang Varieties. The second factor was treatment of plant spacing (J), consist of : J1 = 20x20 cm, J2 = 20x25 cm, J3 = 20x30 cm and J4 = 20x35 cm. The result of this research shows that the interaction between ciherang varieties with plant spacing of 20 x 35 cm given the highest number of rice plants tillers 24.33 stems/clumps, and cisantana varieties with plant spacing of 20 x 25 cm given the highest number of rice plants tillers 22,67 stems/clumps at 75 Days After Planting (DAP). The interaction between ciherang varieties with plant spacing 20x25 cm produce dry grain weight 6.37 tons/ha. While cisantana varieties with plant spacing of 20 x 35 cm produce dry grain weight 6.22 tons/ha. Ciherang varieties provide growth (plant height, number of leaves at 30, 45, 60 and 75 DAP, and number of productive tillers) better than cisantana varieties, and 20 x 25 cm plant spacing gave better growth and yield of rice than other plant spacing.